High efficiency of bamboo-like carbon nanotubes on functionalized graphite felt as electrode in vanadium redox flow battery. Issue 104 (26th October 2016) - Chang, Yu-Chung; Shih, Yu-Chen; Chen, Jian-Yu; Lin, Guan-Yi; Hsu, Ning-Yih; Chou, Yi-Sin; Wang, Chen-Hao
Abstract : B-CNT/TA-GF has high efficiency and good stability for VRFB application. Abstract : Bamboo-like carbon nanotubes (B-CNT) were directly grown on graphite felt (B-CNT/TA-GF) by chemical vapor deposition for use as positive and negative electrodes in a vanadium redox flow battery (VRFB); the graphite felt was functionalized by acid activation and thermal treatment before the growth of B-CNT. B-CNT/TA-GF shows excellent activity and high reversibility in catalyzing the redox reaction of vanadium ions, in which the ratio of the redox peak current densities is close to 1 and the separation of the redox peak potentials is only 0.181 V. VRFBs using B-CNT/TA-GF show 81.0% energy efficiency, which is superior to those using untreated GF (68.3%), acid-treated GF (77.5%) and acid- and thermal-treated GF (76.1%). Thus, the VRFB using B-CNT/TA-GF yields a low iR drop, high efficiency, and high capacity, which may arise from its large surface area, large amount of oxygen functional groups, low internal resistance, favorable sp 2 carbon content, and nitrogen dopant on the surface of the CNTs, all of which make the electrodes in a VRFB efficient.